Women’s Representation in Mandailing Patriarchal Culture: A Corpus-Assisted Critical Discourse Analysis of Local News Media: Representasi Perempuan dalam Budaya Patriarkal Mandailing: Analisis Wacana Kritis Berbasis Korpus pada Media Berita Lokal - Hanifah Oktarina; Eri Kurniawan; Rinaldi Supriadi (Jurnal Adat dan Budaya Indonesia, 2026)
Media plays a crucial role in shaping public discourse and reinforcing cultural ideologies, particularly regarding gender representation. In Mandailing society, where patriarchal norms are prevalent, media discourse provides valuable insights into the positioning of women in social and political spheres. This study investigates the linguistic representations of women in local online news media in Mandailing and explores how these discourses either uphold or challenge patriarchal values. Utilizing a Corpus-Assisted Discourse Studies (CADS) approach, the research combines quantitative corpus analysis with qualitative Critical Discourse Analysis (CDA). The data consists of 180 news articles published between 2020 and 2025 from four local digital news platforms. AntConc 4.3.1 was used to perform word list, concordance, and collocation analyses to uncover patterns in word frequency and lexical associations. These patterns are interpreted through Van Dijk’s socio-cognitive model to understand how discursive structures reflect underlying social ideologies. The analysis reveals that while the media often depicts women as active agents and supporters of solidarity, it also contains elements that reinforce traditional roles and patriarchal norms. The findings underscore the complexity of gender representation in this local context, suggesting that media portrayals can significantly influence societal perceptions of gender roles, promoting both empowerment and the reinforcement of patriarchal values.